Morphometric study of the acetabular in malay population normal hips and its clinical applications - Baharuddin, Mohd Yusof; Zulkifly, Ahmad Hafiz; Abdul Kadir, Mohammed Rafiq; Sa'at@Yusof, Azlin; Abd. Aziz, Azian; Muhammad Hisyam, Lee (A N S I Network, 2011)
The morphology study of acetabular is vital in clinical applications particularly through planning before acetabulum surgery and for determining the dysplastic hip. Several studies show that the acetabular morphology varies between populations; which lead to the difficulty to align the implant by following western standard. This prospective, cross sectional study focused on Malay population by providing essential information regarding normal value of acetabular which will enhance knowledge of the anatomical aspects and eventually aiding the acetabular cup placement during Total hip arthroplasty (THA). The acetabular images were obtained using computed tomography scanner and the measurement has been taken from 120 hips. We excluded from the study: pregnant woman, experienced hips injury, wearing implant or prosthesis. Our data were compared using Kolmogorov-Smirnov method and t-test. The findings for the acetabular as follows: center edge angle (CE) 31.69±5.48°; acetabular index angle (AA) 4.27±4.03°; acetabular angle of Sharp 42.35±3.24°; acetabular version (AcetAV) 14.99±5.05°; acetabular depth (AD) 15.49±1.70 mm; joint space width (JSW) 5.84±0.80 mm; anterior acetabular sector angle (AASA) 61.19±6.72°; posterior acetabular sector angle (PASA) 92.80±6.27°. This study documents for the first time the acetabular morphometric value on Malay population which will improve data, aiding the orthopedic surgeons during acetabular placements in THA and designing better implant.